Toward the Meiji revolution the search for "civilization" in nineteenth century Japan - Karube, Tadashi 1965-; Noble, David (2019)
In 2018 Japan marked the 150th anniversary of the collapse of the Tokugawa shogunate and the establishment of a new government under Emperor Meiji. This was not simply a transfer of political authority but instead signaled revolutionary transformation in Japan, including the abolition of the domains and the formation of a modern nation-state in the years that followed. A period of radical social change was ushered in, with the abolition of the class system, the introduction of Western thought and technology, the development of mass media, and the establishment of constitutional government. The impact on Japan of diplomatic, economic, and cultural pressure from the United States and other Western powers from 1853 onward was previously thought to be the immediate catalyst of this 'Meiji Revolution.' But Japan's modern transformation was rooted in a much deeper process of social and intellectual development that gradually unfolded throughout the latter half of the Tokugawa period. Surveying a diverse group of thinkers spanning the Tokugawa and early Meiji years -- Ogyu? Sorai, Yamagata Banto?, Motoori Norinaga, Rai San'yo?, Fukuzawa Yukichi, Takekoshi Yosaburo?, and others -- this ambitious book liberates modern Japanese history from the stereotypical narrative of 'Japanese spirit and Western technique,' offering a detailed examination of the elements in Tokugawa thought and culture that spurred Japan to articulate its own unique conception of civilization during the course of the nineteenth century." From the dustjacket.
Meiji restoration or Meiji revolution? -- The long revolution -- History in reverse -- The Voltaire of Osaka -- Is commerce evil? -- The age of economics -- Another side of Motoori Norinaga -- A new cosmology and the concept of Ikioi -- Ikioi as the motive force in history -- A farewell to the Ho?ken system -- The advent of "civilization".
Originally published in Japan by Shincho?sha, 2017.
Includes bibliographical references (pages 241-248).
Keywords: Social science -- Japan -- Philosophy -- History -- 19th century; Japan -- History -- Restoration, 1853-1870.